Consultoria colaborativa escolar na área da deficiência visual ocular e cortical - Marques, Lydia da Cruz (Universidade Federal de São Carlos, 2013)
The literature has pointed to an increase in the incidence of children with visual impairments associated with neurological disorders and other disabilities, but the educational implications of the association of such impediments is considered a minor theme in the training of special education teachers. The present study aimed to develop and evaluate a collaborative consultation program in the field of visual impairment with a team of professionals of a special school for students with intellectual disabilities. The participants were the research/consultant, five teachers, two class assistants, a speech therapist, a physical therapist, a psychologist and an occupational therapist, plus 46 students with ages between 7 and 37 years. The study was carried out in three stages: preliminary step of conducting ethical procedures; Study-1, the diagnosis of institutional conditions; and Study-2, the intervention. The latter involved: a) theoretical training of 35 hours of lessons; b) practice based on case studies based on the development of a visual evaluation process of students, with the purpose of raising subsidies for educational planning and to apply the theoretical knowledge in practice; and c) final evaluation of the consultation/training program. The results of student s characterization showed that 30.4% were diagnosed with cerebral palsy; 30.4% with intellectual disabilities; 19.6% with Down syndrome, and 19.6% with other diagnoses. 83% of the students have already been through ophthalmological inspection with an average age of 4.2 years in first query. Two students were diagnosed with optic nerve atrophy and congenital cataracts, which was not reported by the parents to the school. As for the observation of visual difficulties, the parents have made 11 references, whereas the professionals made only 3. The results of the evaluation process of visual changes, duly complemented by medical information, were: 16 students (34.8%) showed no detected changes; 20 (43.5%) with minor changes (strabismus, refraction errors); 3 (6.5%) with visual impairment of ocular origin; 3 (6.5%) with cortical visual impairment; 1 (2.1%) with ocular and cortical visual impairment; and 3 (6.5%) with suspicion of visual impairment. The visual impairment was predominant among the cases of cerebral palsy. The case studies resulted in referrals to ophthalmological consultations, guidance to parents, propositions of pedagogical strategies, in addition the adjustment of materials and environment. The results concerning the evaluation of the collaborative consultation program showed that it was satisfactory regarding the professional development of the consultant and the consultees and regarding the possibilities of solving the addressed problem. The study highlights the need of ophthalmic and visual development assessment among students with intellectual and multiple disabilities and emphasizes the importance of collaborative practice between specialists, family and school professionals to an understanding of the problem of a student with visual impairment associated with intellectual or multiple disabilities. In addition, it suggests the need of a support network for teachers of special education, of generalist formation, what also includes teachers specialized in the visual impairment area, as well as other professionals with technical knowledge.
Collaborative school consultation in the field of oculalr and cortical visual impairment
Keywords: Educação especial; Baixa visão; Deficiência visual cortical; Deficiência intelectual; Deficiência múltipla; Consultoria colaborativa; Cegueira cortical; Paralisia cerebral; Formação em recursos humanos; Low vision; Cortical blindness; Special education; Cerebral palsy; Mental retardation; Training program; Collaborative consultation; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL